The Relationship Between Internal Auditors’ Personal Characteristics, Digital Forensic Technology, and the Ability to Identify Fraud Red Flags in Financial Statements - Audry Leiwakabessy; Ennis Sarenah Kriekhoff (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Financial statement fraud has become more complex in the information age, exposing internal auditors to various challenges in identifying fraud red flags. Objective: This research analyzes the effects of personal characteristics and digital forensic technology on internal auditors’ ability to detect fraud red flags and examines how these two variables interact with each other. Methods: This study used a quantitative approach with a cross-sectional survey design. Primary data were collected through structured questionnaires administered to 25 purposively selected internal auditors from public companies listed on the Indonesia Stock Exchange. The data were analyzed using multiple regression and moderation analysis with SPSS version 26. Results: The multiple regression analysis revealed that internal auditors’ personal characteristics significantly predicted fraud detection ability (β = 0.487, p = 0.005), as did digital forensic technology (β = 0.298, p = 0.030). The moderation analysis indicated a significant interaction effect (β = 0.018, p = 0.036, ΔR² = 6.5%), suggesting that the two variables synergistically enhance fraud detection. The combined model explained 62.4% of the variance in red flag identification (R² = 0.624, F = 18.267, p < 0.001). Conclusion: The study concludes that combining strong auditors’ personal characteristics with appropriate digital forensic technology produces a synergistic effect that significantly enhances fraud red flag detection (ΔR² = 6.5%). Organizations are recommended to invest concurrently in auditor competency development and digital forensic infrastructure, as the interaction effect demonstrates that dual investment yields outcomes exceeding the sum of individual contributions.